(untitled) (Patan Prospective Journal, 2024)
This paper shows that history is portrayed as a fiction in postmodern fiction. As postmodern fiction is an art form, it narrates history in the form of a story. So, the postmodern fiction becomes the fusion of history and fiction. In other words, it is structured as rewriting of history challenging the traditional history. It deconstructs the traditional history of fictionalizing history. The narrative becomes more important than the facts and information. Since the postmodern era is the era of questioning reality, truth, facts and so on which were judged objectively, the history is written and studied subjectively instead of objectively. Regarding objectives of the research, the major objective of the research is to explore how postmodernists fictionalize history. Likewise, its objective are to discover self-reflexivity, multiple identities and metanarrative strategy in postmodern fictions. The research analyses that traditional concept of history, which focuses on the chronological order of organizing events in writing history or historical fictions, has changed. The history is represented in a fragmentary form without having linear plot but focusing on multiple identity issues which traditional fictions failed to do, which also indicates that the great narratives of emancipation and a linear, progressive history have ended. The research adopts qualitative approach as a methodology. For textual analysis, Hayden White theory of history is applied. White’s argument about history “. . . a historical narrative is not only a reproduction of the events reported in it, but also a complex of symbols which gives us directions for finding an icon of the structure of those events in our literary tradition” (The Historical Text as a Literary Artifact, 227) reflects the deconstructive concept of postmodern history.